2019
DOI: 10.3390/molecules24040703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steaming Processing on Phenolic Profiles and Cellular Antioxidant Activities of Castanea mollissima

Abstract: The intention of this study was to investigate the effect of steaming processing on phenolic profiles and antioxidant activities in chestnuts. Steaming processing at different times and temperatures depicted diverse impacts on free and bound fractions. Though, bound phenolics were stable but long time steaming at higher temperatures tended to improve the levels of phenolics, flavonoids as well as antioxidant activities in chestnut kernels, by up to 60.11% of the original value. Seven phenolic compounds includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…High-performance liquid chromatography (HPLC) with photodiode array detector was applied in this study for phytochemical composition analyzing according to previous study [25]. Mobile phase A: milli Q water with 0.1% trifluoroacetic acid; mobile phase B: chromatographically pure methanol; column: Waters Sun FireTM C18 column (250 mm × 4.6 mm, 5 µm); column temperature: 30 • C; flow rate: 1.0 mL/min.…”
Section: Determination Of Phytochemical Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…High-performance liquid chromatography (HPLC) with photodiode array detector was applied in this study for phytochemical composition analyzing according to previous study [25]. Mobile phase A: milli Q water with 0.1% trifluoroacetic acid; mobile phase B: chromatographically pure methanol; column: Waters Sun FireTM C18 column (250 mm × 4.6 mm, 5 µm); column temperature: 30 • C; flow rate: 1.0 mL/min.…”
Section: Determination Of Phytochemical Profilesmentioning
confidence: 99%
“…Oxygen radical absorbance capacity (ORAC) assay was applied to this study to determine the total antioxidant ability of chestnut kernels according to previous study [25]. Fluorescein was used as fluorescence probe and 2,2'-Aazobis dihydrochloride (ABAP) was used as free radical donor in this study.…”
Section: Evaluation Of Total Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers have studied the phenolic profiles and antioxidant activities of chestnuts collected from various geographical regions and also explored the impact of different processing techniques on phenolic content and antioxidant capacities of chestnuts [9,[12][13][14]. A previous study reported the variation in phenolic content and flavonoids content of Chinese chestnut collected from North China to South region of China [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is important, especially for pasta products, which are consumed immediately after cooking. Zhang et al [48] found that bound phenolics in chestnut kernels were stable. However, prolonged steaming at high temperature improved the levels of phenolics, flavonoids, as well as the antioxidant activity up to 60.11% above the original value.…”
Section: Resultsmentioning
confidence: 99%